Development of Human Resources in Android-based Information System for People with Social Welfare Problems - Arman Arman; Alang Alang; Yusrianto Malago (Universitas Muhammadiyah Sidoarjo, 2021)
The problem in this study is that the process of data collection and final report of Persons with Social Welfare Problems has not been computerized properly so that the process of procurement of goods and distribution of assistance for has not been effective and well target. With the aim of his research To simplify the data collection process and final report so that the process of procurement of goods and distribution of aid is more effective and on target. The object of this research is the Procurement Information System and Distribution of Assistance for Persons with Social Welfare Problems in the Gorontalo-based Gorontalo City Social Service with the method used in designing this information system is a descriptive method that is research aimed at solving problems systematically and factually about the facts studied. The design phase includes, model design, output design, Input design, database design and technology design, to the system testing stage. Analysis of the data where the data obtained in the field will be analyzed in a qualitative manner. Qualitative analysis is used to describe the efforts made in the form of human resource development in the information service system of assistance for people with problems based on android-based social welfare towards smart city. The results obtained show that the application can be made and used.